Directional chitosan/carbon fiber powder aerogel supported phase change composites for effective solar thermal energy conversion and hot compression. (1st December 2022) - Bai, Yaning; Lin, Fankai; Liu, Xianjie; Feng, Jian; Zhu, Xiao; Huang, Zhaohui; Min, Xin; Mi, Ruiyu; Qiao, Jiaxin
Abstract: Solar energy is an important green energy. Its efficient utilization has attracted wide attention. Phase change materials can absorb and release significant amounts of latent heat, which are expected to compensate for the intermittence and instability of solar energy. In this study, directional chitosan/carbon fiber powder aerogels were successfully prepared as a support matrix by directional freezing technique for encapsulation of phase change materials. Carbon fiber powder with low cost, high thermal conductivity and good light absorption was selected as a light trap and heat conduction reinforcing filler. Paraffin was effectively encapsulated in directional chitosan/carbon fiber powder aerogels via vacuum impregnation. The prepared paraffin/chitosan@carbon fiber powder composites (PA/CS@CFP) can achieve a high load rate (>94 %) and maintain good encapsulation capability, high enthalpy (211.9–257.5 J/g), thermal stability, solar-thermal energy conversion and storage capability. The lightweight, directional, high porosity CS@CFP aerogels are good matrices of phase change materials, which can realize the solar-thermal conversion and enhance the thermal response of the composite. Additionally, a human heat pack was developed to provide heating for human comfort after solar charging. PA/CS@CFP composites have great potential for solar energy utilization, waste heat recovery, building energy saving, and hot compression. Graphical abstract: Unlabelled Image Highlights: The composite chitosan (CS) aerogel with oriented pores was successfully prepared using the directional freezing technique. The composite chitosan (CS) aerogel encapsulated PCMs prepared by carbon fiber powder as thermal conductive filler and photon trap were successfully prepared as new composite PCMs. When 30 wt.% of carbon fiber powder is added, the pore size of CS@CFP aerogel remains at 10-20 μm, which can load the PCM better. PA/CS@CFP composite PCM has a high loading rate (> 94%), excellent phase change enthalpy (211.9-257.5 J/g), good shape stability, and solar thermal conversion capability.